2023
DOI: 10.2147/idr.s408567
|View full text |Cite
|
Sign up to set email alerts
|

Profile and Frequency of Mutations Conferring Drug-Resistant Tuberculosis in the Central, Southeastern and Eastern Ethiopia

Abstract: Purpose Advances in molecular tools that assess genes harboring drug resistance mutations have greatly improved the detection and treatment of drug-resistant tuberculosis (DR-TB). This study was conducted to determine the frequency and type of mutations that are responsible for resistance to rifampicin (RIF), isoniazid (INH), fluoroquinolones (FLQs) and second-line injectable drugs (SLIDs) in Mycobacterium tuberculosis (MTB) isolates obtained from culture-positive pulmon… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

8
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(10 citation statements)
references
References 43 publications
8
2
0
Order By: Relevance
“…Similarly, in the current study, amongst INH-resistant isolates, mutations in the kat G was most frequent at codon Ser315Thr1 (95%), while no inh A gene mutation was observed. In agreement with our findings, a recent multicenter study in Ethiopia reported a prevalence of 91.8% for kat G/Ser315Thr1 mutation ( 45 ), and a meta-analysis study that examined INH conferring gene mutations noted a prevalence of 95.8% for kat G315 mutation ( 21 ). The kat G/Ser315Thr1 gene mutation, causing high-level INH resistance was predominant (95%) in the current study and other earlier studies in different parts of Ethiopia ( 21 , 45–48 , 55 , 56 , 61 ).…”
Section: Discussionsupporting
confidence: 92%
See 3 more Smart Citations
“…Similarly, in the current study, amongst INH-resistant isolates, mutations in the kat G was most frequent at codon Ser315Thr1 (95%), while no inh A gene mutation was observed. In agreement with our findings, a recent multicenter study in Ethiopia reported a prevalence of 91.8% for kat G/Ser315Thr1 mutation ( 45 ), and a meta-analysis study that examined INH conferring gene mutations noted a prevalence of 95.8% for kat G315 mutation ( 21 ). The kat G/Ser315Thr1 gene mutation, causing high-level INH resistance was predominant (95%) in the current study and other earlier studies in different parts of Ethiopia ( 21 , 45–48 , 55 , 56 , 61 ).…”
Section: Discussionsupporting
confidence: 92%
“…In this study, two RIF-resistant isolates ( rpo BWT6 and rpo BWT7) had shown a mutation or missing WT band, but no corresponding MUT band, and were classified as unknown genetic changes. This proportion of isolates with unknown mutations is similar to other studies from a recent multicenter study, Ethiopia (13.6%) ( 45 ), Addis Ababa, Ethiopia (15.8%) ( 55 ), Southern Ethiopia (14.7%) ( 56 ), and elsewhere, a large, multisite diagnostic study (13%) ( 57 ). This could be due to the mutations occurring outside the analyzed codon regions (drug-resistance determining regions) which LPAs unable to evaluate/detect ( 58 ).…”
Section: Discussionsupporting
confidence: 87%
See 2 more Smart Citations
“…Additionally, in this case report, we identified the gyrA mutation at codon A90V , which was responsible for FQs resistance in MTB isolates. This mutation was also the most common type in the previous studies in Central, and Southeastern Ethiopia and a laboratory-based surveillance study in Ethiopia [21] , [22] . In this case report, the development of second-line drug gene mutations in a drug-resistant MTB strain may be due to several factors, such as poor adherence to medication, drug malabsorption, incomplete or irregular treatment, inappropriate drug selection, dosing errors, or treatment duration, which can also contribute to the development of drug resistance [23] .…”
Section: Discussionsupporting
confidence: 55%